Perancangan PLTA Pico-Hydro menggunakan Tabung Hydrocyclone dan Turbin Kaplan melalui Solusi Numerik Runge-Kutta: Indah Permatasari, Abdul Hakim Prima Yuniarto - Indah Permatasari Indah Permatasari; Abdul Hakim Prima Yuniarto Abdul Hakim Prima Yuniarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
Designing of the Pico-hydrowater Power Plan which uses Kaplan turbine applies water flow within Hydrocyclone tube. Kaplan turbines can move with angular velocity following fluid velocity analyzing the movement converter system. Equation of movement formulated by applying Euler-Lagrange, therefore, generating a differential equation. The differential equation iterated by the Runge-Kutta Method which is one of the numerical solutions. The movement converter system consists of 5 wheels with 1st wheel spindle with 2nd wheel. The 2nd and 3rd wheels are interconnected and the 4th wheel is connected to the 5th wheel to generate electricity generation. The results obtained by the flow of water can rotate Kaplan turbines with a force of 50N. Maximum angular velocity of 5500 rad/s on the 5th wheel. The rotation speed of the wheels on the converter system will increase with time.